Sustainable Livelihood in Post-Disaster Tourism: Lesson Learned from Merapi Tourism Site - Sakir Sakir; Dyah Mutiarin; Rivaldi Alan Saputra; Fairuz Arta Abhipraya (Ministry of Tourism and Creative Economy/Tourism and Creative Economy Agency Republic of Indonesia, 2024)
This research aims to explore the practice of the Sustainable Livelihood Tourism Framework (SLTF) in post-disaster management in the Mount Merapi area, Sleman, Yogyakarta. The focus of SLTF achievement in this study encompasses ecological, economic, sociocultural, and institutional dimensions. Research on the SLTF has indeed become a significant focus in tourism studies. However, most of these studies are confined to a single research methodology, resulting in limited scope and a lack of comprehensive discussion. This study used a mixed-method approach with an explanatory sequential design. The study found that tourism positively impacts the increase of economic activities in the community. However, on the ecological side, tourism presence degrades environmental quality due to issues such as carbon emissions, industrial waste, climate change, the greenhouse effect, illegal logging, and illegal mining. Furthermore, other policies were identified, such as mineral water mining permits that degrade the environment and the establishment of landfill sites in the Kaliurang area, which spoils the natural beauty. Tourism practices also have a negative impact on institutional aspects, as the community perceives government policies as too complex and not meeting their expectations. Lastly, in the socio-cultural aspect, tourism preserves traditional values, as tourists tend to respect them. This mixed-method approach underscores the need for balanced strategies that address environmental concerns while maximizing economic benefits, improving institutional involvement, and supporting socio-cultural enhancement.